2017
DOI: 10.1371/journal.pone.0169909
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Pressure Ulcers in an Older Adult Population Hospitalized for Hip Fractures: A Prognostic Cohort Study

Abstract: BackgroundOlder adult patients with fragility hip fractures constitute a population at high risk for complications, in particular pressure ulcers. The aim was to evaluate the incidence of pressure ulcers and potential predictive factors.Methods and FindingsA prospective multicentric prognostic cohort study in orthopedic wards in three Italian public hospitals. Participants were all consecutive patients 65 years of age or older diagnosed with a fragility hip fracture. Outcomes were incidence of pressure ulcers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 25 publications
5
56
4
4
Order By: Relevance
“…The higher percentage of Stage 1 PIs in the present study may indicate, to some extent, timely assessments and early detection of changes in skin status. Our findings contrasted with the conclusion of several previous studies that Stages 2 and 3 are the most common PI stages …”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The higher percentage of Stage 1 PIs in the present study may indicate, to some extent, timely assessments and early detection of changes in skin status. Our findings contrasted with the conclusion of several previous studies that Stages 2 and 3 are the most common PI stages …”
Section: Discussioncontrasting
confidence: 99%
“…This study has shown that the risk of PIs was higher for people aged over 65 years than for those aged 18 to 65 years. This result was consistent with the majority of published findings, which have shown a higher risk of PI at older age . However, Wielen et al and Magny et al found no significant association between age and the occurrence of PIs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations